Measuring long-term inequality of opportunity - Rolf Aaberge; Magne Mogstad; Vito Peragine (Statistics Norway, Research Department, 2010)
In this paper, we introduce and apply a general framework for evaluating long-term income distributions according to the Equality of Opportunity principle (EOp). Our framework allows for both an ex-ante and an ex-post approach to EOp. Our ex-post approach relies on a permanent income measure defined as the minimum annual expenditure an individual would need in order to be as well off as he could be by undertaking inter-period income transfers. There is long-term ex-post inequality of opportunity if individuals who exert the same effort have different permanent incomes. In comparison, the ex-ante approach focuses on the expected permanent income for individuals with identical circumstances. Hence, the ex-ante approach pays attention to inequalities in expected permanent income between different types of individuals. To demonstrate the empirical relevance of a long-run perspective on EOp, we exploit a unique panel data from Norway on individuals' incomes over their working lifespan.
Keywords: D71; D91; I32; 330; equality of opportunity; social welfare; inequality; permanent income; intertemporal choice; ex-ante; ex-post